Generation of a Recombinant Porcine Reproductive and Respiratory Syndrome Virus Stably Expressing Two Marker Genes - Wang, Hao; Xie, Xin; He, Wei; Wang, Yuxu; Ren, Tongwei; Ouyang, Kang; Chen, Ying; Huang, Weijian; Wei, Zuzhang (Frontiers in Veterinary Science, 2020)
Porcine reproductive and respiratory syndrome virus (PRRSV) has been used as a gene expression vector in the development of vaccines. Most of these recombinant PRRSV vectors express only a single foreign gene through either an internal insertion in the hypervariable region of nsp2 or expression cassette and some of these recombinant vectors are genetically unstable. Here, we combined internal insertion in nsp2 and expression cassette methods to generate a novel recombinant PRRSV stably expressing the red fluorescence protein (RFP) and the green fluorescence protein (GFP) genes. Biological characteristic analysis of the recombinant PRRSV carrying the two marker genes, rGX-RFP-GFP, showed that it displayed similar growth kinetics and yet it yielded less infectious viruses when compared to the parental virus rGXAM. Co-expression of both the RFP and GFP was observed using confocal fluorescence microscopy when the rGX-RFP-GFP viruses infected MARC-145 cells. Furthermore, the PRRSV-based two-marker gene expression vector is genetically stable during 20 serial passages in MARC-145 cells. These data demonstrate that it is possible to express two interested immunogens from a single PRRSV vector.